pH-dependent localization of Btn1p in the yeast model for Batten disease - Devin M. Wolfe; Sergio Padilla-Lopez; Seasson Phillips Vitiello; David A. Pearce (The Company of Biologists, 2011)
SUMMARY Btn1p the yeast homolog of human CLN3, which is associated with juvenile Batten disease has been implicated in several cellular pathways. Yeast cells lacking BTN1 are unable to couple ATP hydrolysis and proton pumping activities by the vacuolar ATPase (V-ATPase). In this work, we demonstrate that changes in extracellular pH result in altered transcription of BTN1, as well as a change in the glycosylation state and localization of Btn1p. At high pH, Btn1p expression was increased and the protein was mainly located in vacuolar membranes. However, low pH decreased Btn1p expression and changed its location to undefined punctate membranes. Moreover, our results suggest that differential Btn1p localization may be regulated by its glycosylation state. Underlying pathogenic implications for Batten disease of altered cellular distribution of CLN3 are discussed.